Site disparities in apoptotic variants as predictors of risk for second primary malignancy in patients with squamous cell carcinoma of the head and neck - Sun, Yan (BMC Cancer, 2016)
BACKGROUND: FAS/FASL promoter variants are considered in altering transcriptional activity of those genes and consequently alter regulation of cell death. However, no studies have investigated whether tumor sites contribute to the association between FAS/FASL polymorphisms and risk for second primary malignancy (SPM). METHOD: In this study, FAS670 A > G, FAS1377 G > A, FASL124 A > G, and FASL844C > T polymorphisms were genotyped in 752 OPC and 777 non-OPC patients. Both univariate and multivariable cox proportional hazard models were used to assess the associations. RESULTS: The univariate and multivariable analyses showed that patients with index OPC and FASL844 CT/TT genotype had significantly increased risk of SPM (cHR, 2.5; 95 % CI, 1.1–5.8, P = 0.043 and aHR, 2.7; 95 % CI, 1.2–6.0, P = 0.032) compared with those with FASL844 CC genotype as the reference group, while index non-OPC patients with FAS670 AG/GG and FasL844 CT/TT genotypes had significantly increased risk of SPM (cHR, 2.2 and 1.8; 95 % CI, 1.2–5.7 and 1.1–3.2; and P = 0.04 and 0.041, respectively and aHR, 2.4 and 1.7; 95 % CI, 1.1–5.1 and 1.0-3.0; and P = 0.043 and 0.049, respectively) compared with their corresponding AA and CC genotypes . Moreover, patients carrying more FAS/FASL variants significantly increased risk of SPM among index non-OPC patients. The stratified analysis showed that smoking status differently modified the associations between FAS/FASL polymorphisms and risk of SPM among index non-OPC from OPC patients. CONCLUSION: These results suggested that FAS/FASL polymorphisms might significantly modify SPM risk among patients with SCCHN in a tumor site-specific manner.